2017
DOI: 10.1016/j.cancergen.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling, pathway analysis and subtype classification reveal molecular heterogeneity in hepatocellular carcinoma and suggest subtype specific therapeutic targets

Abstract: A very low 5-year survival rate among hepatocellular carcinoma (HCC) patients is mainly due to lack of early stage diagnosis, distant metastasis and high risk of postoperative recurrence. Hence ascertaining novel biomarkers for early diagnosis and patient specific therapeutics is crucial and urgent. Here, we have performed a comprehensive analysis of the expression data of 423 HCC patients (373 tumors and 50 controls) downloaded from The Cancer Genome Atlas (TCGA) followed by pathway enrichment by gene ontolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 74 publications
3
25
0
Order By: Relevance
“…Overexpression of CDK1 is associated with poor clinicopathologic features and is predictive of recurrence. This study also showed that CDK1 is a crucial G 2 –M modulator in cell cycle progression and cell proliferation of HCC . In the case of HCC, CDK1 is overactive when compared to comparable non‐tumor tissues .…”
Section: Biology and Regulation Of Cdks In Hccsupporting
confidence: 61%
See 1 more Smart Citation
“…Overexpression of CDK1 is associated with poor clinicopathologic features and is predictive of recurrence. This study also showed that CDK1 is a crucial G 2 –M modulator in cell cycle progression and cell proliferation of HCC . In the case of HCC, CDK1 is overactive when compared to comparable non‐tumor tissues .…”
Section: Biology and Regulation Of Cdks In Hccsupporting
confidence: 61%
“…This study also showed that CDK1 is a crucial G 2 -M modulator in cell cycle progression and cell proliferation of HCC. 42 In the case of HCC, CDK1 is overactive when compared to comparable nontumor tissues. 23 As expected, HCC tissues consistently show elevated CDK1 expression in western blot and real- Figure 1 Cell cycle-associated development of hepatocellular carcinoma (HCC).…”
Section: Biology and Regulation Of Cdks In Hccmentioning
confidence: 99%
“…Cancer cell is characterized as uncontrolled cell growth, migration, and invasion that resulted from abnormal expression of many protein‐coding genes and abnormal activation signaling pathways (Agarwal, Narayan, Bhattacharyya, Saraswat, & Tomar, ; Jin et al, ). In addition to protein‐coding genes, noncoding RNAs including circular RNAs and microRNAs (miRNAs) are also reported to involve in HCC carcinogenesis (Xiong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, having family history of liver cancer showed four times the risk of liver cancer, and if it was from first‐degree relative, the risk increase was five times, which was stronger than the associations reported in former observations . Inheritance is believed to play a role in liver carcinogenesis and genetic epidemiologic studies kept searching for and reporting susceptible loci . Meanwhile, family‐aggregated environmental exposures also increased the risk, and the associations between aflatoxin intake though mildew‐contaminated food, unsafe raw water and liver cancer risk were confirmed in this study and previous literature …”
Section: Discussionmentioning
confidence: 99%